2017
DOI: 10.1136/bjsports-2017-097791
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of potential long-term effects of sport-related concussion

Abstract: ObjectiveSystematic review of possible long-term effects of sports-related concussion in retired athletes.Data sourcesTen electronic databases.Study selectionOriginal research; incidence, risk factors or causation related to long-term mental health or neurological problems; individuals who have suffered a concussion; retired athletes as the subjects and possible long-term sequelae defined as >10 years after the injury.Data extractionStudy population, exposure/outcome measures, clinical data, neurological exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
338
5
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(357 citation statements)
references
References 74 publications
7
338
5
7
Order By: Relevance
“…TBI is a common cause of enduring cognitive deficits and behavioral alterations in the general public, contact sport athletes, and military personnel (Bogdanova and Verfaellie 2012; Manley et al 2017). Moreover, while mTBI may not cause overt neuronal degeneration in the short-term, repeated concussions can result in a delayed progressive neurodegenerative process called chronic traumatic encephalopathy (Vos et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…TBI is a common cause of enduring cognitive deficits and behavioral alterations in the general public, contact sport athletes, and military personnel (Bogdanova and Verfaellie 2012; Manley et al 2017). Moreover, while mTBI may not cause overt neuronal degeneration in the short-term, repeated concussions can result in a delayed progressive neurodegenerative process called chronic traumatic encephalopathy (Vos et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Subconcussive impacts are defined as transfer of mechanical energy to the brain causing presumed axonal or neuronal injury in the absence of clinical signs or symptoms 112. It is unclear if a biomechanical threshold or other factors lead to injury or if this entity qualifies as injury since it does not seem to be associated with neuropsychological changes 113.…”
Section: Risks Related To Concussionmentioning
confidence: 99%
“…Repetitive neurotrauma sustained during a career in boxing has been reported to be associated with chronic brain damage in some former athletes since the 1920s [103], but it has only been associated with former National Football League (NFL) players more recently. A review on this issue conducted by Manley and colleagues [104] reported that there is emerging evidence that some retired NFL players have mild cognitive impairment [105,106], neuroimaging abnormalities [107,108], and differences in brain metabolism [109] [8]. An initial period of 24-48 hours of both relative physical rest and cognitive rest is recommended before commencing the GRTP process.…”
Section: Potential Longer Term Concernsmentioning
confidence: 99%
“…For a comprehensive review of this literature see Manley et al [104], Iverson et al [111], Gardner et al [112], Randolph et al [113], and McCrory et al [114].…”
Section: Potential Longer Term Concernsmentioning
confidence: 99%